Retelling Story Through A Short Clip At Islamic Boarding School - Anisa Izza Faudzia; Dzul Rachman (Departement of Mathematics Education, 2024)
This research aims to investigate students' speaking skills through the retelling technique using short clips and how students respond to the implementation of retelling techniques in speaking skills. The research uses a mixed methods approach. Data are gathered through retelling short clips and conducting pre-tests and post-tests. Both qualitative and quantitative analysis techniques are utilized for data analysis. Quantitative analysis is employed to determine differences in student learning outcomes by comparing pre-test and post-test scores. Meanwhile, qualitative analysis is used to describe or interpret the results of observations obtained from qualitative data. Results indicate significant enhancements in both accuracy and fluency post-intervention, underscoring the effectiveness of the retelling technique supported by multimedia. Findings suggest that integrating short clips into language teaching can boost students' confidence and proficiency in speaking English. The study recommends further exploration into diverse multimedia forms and longitudinal studies to validate these findings across various educational contexts.